ANALISIS KINERJA OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN JAWA TENGAH DALAM RANGKA PENYELESAIAN LAPORAN MASYARAKAT - Tri Yanti Nur Irson Sitorus; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Maladministration is a behavior that is not in accordance with the principles of good public service. The Indonesian Ombudsman Representative of Central Java is the representative of the Ombudsman of the Republic of Indonesia in Central Java whose function is to monitor and prevent maladministration actions carried out by following up and completing public reports /complaints. The purpose of this study was to analyze and describe the performance of the Indonesian Ombudsman Representative in Central Java in order to resolve community reports. The research method used is descriptive qualitative method. The indicators used to assess performance in this study are productivity, service quality, responsiveness, responsibility, and accountability. In addition, it is also seen from the supporting factors and obstacles to organizational performance. The results showed that the productivity of the Republic of Indonesia Ombudsman Representative in Central Java was not maximal due to the completion of reports that the community had not yet reached the target. The quality of service in completing reports is also not optimal, because the Ombudsman is still slow in handling public reports. The responsiveness of the Republic of Indonesia Ombudsman to the Central Java Representative has not been maximized due to limited expertise in reviewing and discussing the wishes of the reporter and the reported party. The responsibility of the Republic of Indonesia Ombudsman Representative in Central Java is not maximal and are not accountable and transparent to the community. The factors that hamper performance are the lack of quantity and quality of human resources in completing reports, the absence of work system mechanisms, lack of facilities and infrastructure, budget constraints, lack of public knowledge about the existence of the Ombudsman in Central Java, and leadership and team driving Ombudsman's performance.